2022
DOI: 10.1021/acsanm.2c02986
|View full text |Cite
|
Sign up to set email alerts
|

Negative Tone Metallic Organic Resists with Improved Sensitivity for Plasma Etching: Implications for Silicon Nanostructure Fabrication and Photomask Production

Abstract: Metal–organic materials such as [NH2(CH2–CHCH2)2][Cr7NiF8(Pivalate)16] can act as negative tone resists for electron beam lithography (EBL) with high-resolution patterning of sub-40 nanometer pitch while exhibiting ultrahigh dry etch selectivities >100:1 and giving line dose exposures >11,000 pC/cm. It is clear that the resist sensitivity is too low to be used to manufacture the latest nanoscale photomasks that are suitable for extreme ultraviolet lithography. Therefore, the focus of this work here is to impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…This resulted in defects or rough edges in the obtained patterns (Figure d). Upon single-line exposure, ,, Films A and B exhibited limiting resolution. Line patterns with a critical dimension (CD) of 13 nm were achieved for both films at 60 and 5 nC/cm respectively, with Film A showing more uniform line edges (Figures g and S51).…”
Section: Results and Discussionmentioning
confidence: 99%
“…This resulted in defects or rough edges in the obtained patterns (Figure d). Upon single-line exposure, ,, Films A and B exhibited limiting resolution. Line patterns with a critical dimension (CD) of 13 nm were achieved for both films at 60 and 5 nC/cm respectively, with Film A showing more uniform line edges (Figures g and S51).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Nonetheless, the patterned HRR resist has been shown to exhibit an unparalleled etch selectivity toward organic (e.g., organic planarizing layers and amorphous carbon) and inorganic (Si, W) underlayers, due to the formation of a chromium oxide hardmask that is particularly resistant to reactive ion etch (RIE) plasma 29 . At the printed feature size of 25 nm L/S, the {Cr7Ni} resist has a demonstrated etch selectivity of 99:1 to silicon, 30 and even larger selectivities could be achieved at larger pitches, 28 which compares favorably to the etch selectivities of common resists to silicon at 100-nm pitch, such as PMMA (2.0:1), ZEP520A (2.9:1), and HSQ (4.2:1) 31 . Together with previously demonstrated spatial resolution down to sub 10-nm lines, 28 , 29 the HRR platform can simplify complex multilayer stacks that utilize a highly etch resistant metal hardmask layer under a high resolution resist by combining both layers into one.…”
Section: Methodsmentioning
confidence: 99%
“…Another benefit of using metal-containing resist materials, specifically as etch masks, is their increased etch resistance when compared to conventional polymer resists. In a recent study, a Cr-containing metal-organic resist demonstrated an Si etch selectivity of nearly 100:1 [31] , while ZEP520A, a typical organic photoresist, had an etch selectivity of approximately 1:1 for similar etch conditions [32] .…”
Section: Introductionmentioning
confidence: 99%